2021
DOI: 10.3389/fmicb.2020.579929
|View full text |Cite
|
Sign up to set email alerts
|

Population Genetic Analysis of the Theileria annulata Parasites Identified Limited Diversity and Multiplicity of Infection in the Vaccine From India

Abstract: Background: Apicomplexan parasite Theileria annulata causes significant economic loss to the livestock industry in India and other tropical countries. In India, parasite control is mainly dependent on the live attenuated schizont vaccine and the drug buparvaquone. For effective disease control, it is essential to study the population structure and genetic diversity of the Theileria annulata field isolates and vaccine currently used in India.Methodology/Results: A total of 125 T. annulata isolates were genotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 44 publications
3
14
0
Order By: Relevance
“…Genetic diversity is considered a raw material for the evolution of organisms [29]. The long-term survival of T. annulata in host animals is facilitated by the protozoan's genetic diversity, which helps the parasite escape the host's immune response [31]. T. annulata achieves this genetic diversity through chromosomal recombination in tick vectors during its sexual reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic diversity is considered a raw material for the evolution of organisms [29]. The long-term survival of T. annulata in host animals is facilitated by the protozoan's genetic diversity, which helps the parasite escape the host's immune response [31]. T. annulata achieves this genetic diversity through chromosomal recombination in tick vectors during its sexual reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…Tick transmitted diseases with high infection in the bovine population of Bihar with Theileria spp., A marginale and B. bigemina and their co-infection has been frequently reported (Kala et al 2018;Kumar et al 2021;Prabhakaran et al 2021;Roy et al 2021). The study indicated that the endemic region had high (76.67%) infection of tick-transmitted hemo-parasite in selected crossbred cattle based on conventional Giemsa blood smear examination (Fig 1).…”
Section: Resultsmentioning
confidence: 75%
“…Tick transmitted diseases with high infection in bovine population of Bihar with Theileria spp., A marginale , and B. bigemina and their co-infection has been frequently reported (Kala et al 2018; Kumar et al 2019; Kumar et al 2021; Prabhakaran et al 2021; Roy 2021). Our finding also suggest high rate of infection of these hemo-parasite and association of more than one type parasite in the animals screened by GSBS.…”
Section: Discussionmentioning
confidence: 99%